PENGGUNAAN MEDIA SOSIAL WHATSAPP TERHADAP MOTIVASI BELAJAR DAN KEMAMPUAN MATEMATIS: A REVIEW OF RESEARCH IN INDONESIA - Martini Martini; Cahaya Bilkis; Muchamad Subali Noto; Irmawati Liliyana Kusuma Dewi (Jurnal Lebesgue)
The internet is expected to help educators keep up with the times when providing materials and increase students' motivation to learn especially mathematics subjects. Students' motivation and mathematical abilities are developmental, interdependent, and influenced by educational experiences' design. The most widely used internet development is WhatsApp social media. With social media, teachers can form a network of collaborative learning groups online that can save many people's time and energy. This study aims to find out the impact of WhatsApp social media on students' motivation and mathematical ability. The method of this research is a systematic literature review using the PRISMA approach. The result of this study is that the use of WhatsApp has become an interaction and meeting point between teachers and students, which has become limitless, so it can be easier to create a positive relationship. Students can have a greater role in decision-making, collaboration, and engagement in offline and online learning because these relationships can help build active learning